Effect of varying SRT on the performance of MDBR - Chew, Cassandra Siok Kwan. (2012)
Membrane fouling has always been a challenge in membrane systems. Several parameters affect fouling, but extracellular polymeric substances (EPS) has often been reported as the major foulant. Sludge retention time (SRT) has been known to affect the biochemical characteristics of biomass that are responsible for fouling. Since membrane distillation bioreactor (MDBR) is a novel technology, little has been known about the effect of SRT on fouling in MDBR. In this study, the effect of SRT on membrane fouling was examined by determining its effects on the production of EPS, biomass, removal of total organic carbon and total nitrogen, as well as the MDBR flux. It was shown that SRT had significant effect on the biochemical characteristics of the retentate, e.g. higher carbohydrates concentration was observed at the shorter SRT of 10 days, which may have contributed to the faster flux decline observed at SRT 10 days.